THE IMPLEMENTATION OF PARTNER READING STRATEGY IN IMPROVING STUDENTS’ READING COMPREHENSION - Rahmayanti Sri Rejeki; Hasnawati Latief; Radiah Hamid (FKIP Unismuh Makassar, 2021)
This research aims to find out the improvement of student reading comprehension in narrative text through using Partner Reading Strategy at in the 8th Grade of SMP Unismuh Makassar. This research applied Pre-Experimental Method. The research had conducted with treatment, where the class consisted of four meetings. The location of this research was done at the second Grade students’ of SMP Unismuh Makassar with 24 student, the instrument used pre-test and post-test The findings indicated that the application of Partner Reading Strategy is significant to improve the students reading comprehension and it was proved by means score in pre-test was 49. 72 and the post-test was 81.77. It means that the mean score of post-test is greater than the pre-test, and also it is can be concluded that the use of Partner Reading Strategy improved the students’ reading comprehension especially literal comprehension in term main idea and reorganization in term summary